Peroxiredoxin 6 Attenuates Alloxan-Induced Type 1 Diabetes Mellitus in Mice and Cytokine-Induced Cytotoxicity in RIN-m5F Beta Cells. (27th August 2020) - Novoselova, Elena G.; Glushkova, Olga V.; Lunin, Sergey M.; Khrenov, Maxim O.; Parfenyuk, Svetlana B.; Novoselova, Tatyana V.; Sharapov, Mars G.; Novoselov, Vladimir I.; Fesenko, Evgeny E.
Abstract : Type 1 diabetes is associated with the destruction of pancreatic beta cells, which is mediated via an autoimmune mechanism and consequent inflammatory processes. In this article, we describe a beneficial effect of peroxiredoxin 6 (PRDX6) in a type 1 diabetes mouse model. The main idea of this study was based on the well-known data that oxidative stress plays an important role in pathogenesis of diabetes and its associated complications. We hypothesised that PRDX6, which is well known for its various biological functions, including antioxidant activity, may provide an antidiabetic effect. It was shown that PRDX6 prevented hyperglycemia, lowered the mortality rate, restored the plasma cytokine profile, reversed the splenic cell apoptosis, and reduced the β cell destruction in Langerhans islets in mice with a severe form of alloxan-induced diabetes. In addition, PRDX6 protected rat insulinoma RIN-m5F β cells, cultured with TNF- α and IL-1 β, against the cytokine-induced cytotoxicity and reduced the apoptotic cell death and production of ROS. Signal transduction studies showed that PRDX6 prevented the activation of NF- κ B and c-Jun N-terminal kinase signaling cascades in RIN-m5F β cells cultured with cytokines. In conclusion, there is a prospect for therapeutic application of PRDX6 to delay or even prevent β cell apoptosis in type 1 diabetes.